(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To survey drug-related problems (DRPs) and associated factors in outpatients with heart failure at Nguyen Tri Phuong Hospital. Subject and Method: A cross-sectional, retrospective study was conducted on 120 outpatients with chronic heart failure from January 2022 to April 2023. DRPs were identified by clinical pharmacists using the Vimed tool and were re-evaluated by a cardiologist. Results: 90.0% of patients used at least five types of medications. A total of 292 DRPs were detected in 106 patients (88.3%), with an average of 2.4 ± 1.56 DRPs per patient. The most common DRPs included inappropriate drug use (36.3%), drug interactions (33.6%), lack of treatment monitoring (13.0%), and under-prescription (9.9%). Univariate and multivariate analyses showed that co-existing ischemic heart disease, atrial fibrillation and the use of more than 5 medications were associated with the occurrence of DRPs. A total of 269 pharmacist interventions were proposed, with 66.9% receiving physician approval. Conclusion: The study demonstrated the role of clinical pharmacists in detecting DRPs and proposing pharmacist interventions for outpatients with heart failure.